A Passionate Misunderstanding: Orwell's Paris, Miller's China. Issue 3 (2nd April 2016) - Stan, C. M.
ABSTRACT: One of the most famous essays in the sociology of intellectuals, "Inside the Whale" (1940), has been commonly understood as an anomaly: by endorsing Henry Miller's quietism in the face of world-scale disaster, George Orwell seemed to waver from his otherwise exemplary political commitment, later confirmed by famous books such as Animal Farm and 1984 . A close look at the essay's literary career, however, suggests that Orwell might have misread Miller's work, in particular Tropic of Cancer (1934), and engagement with the genealogy and rhetoric of "Inside the Whale" sheds light on Orwell's passionate misunderstanding of the American author's footloose, rootless existence in Paris, that he was too eager to identify with his own experiences of voluntary destitution, recorded only a few years before in Down and Out in Paris and London (1933). This essay revisits "Inside the Whale" and the two books that marked the beginning of Orwell's and Miller's acquaintance, spelling out the nature of their aesthetic and political differences, and shedding light on Orwell's deeply ambivalent stance with regard to political commitment around 1940.